Evaluation of serai kayu (Sygyzium polyanthum) leaves extract as blood pressure lowering agent in hypertensive rat’s model - Jamal, Norfazirah (Universiti Sains Malaysia, 2017)
Syzygiumpolyanthum or “serai kayu” is popular among Kelantanese as traditional antihypertensive medicine. This study aimed to evaluate the effects of oral crude aqueous and methanol extracts of S.polyanthum (AESP and MESP, respectively) on blood pressure of spontaneous hypertensive rat (SHR) and the histopathology improvements on the kidney of treated-SHR. AESP and MESP were prepared using ultrasound-assisted (sonication) extraction technique. The changes of systolic blood pressure (SBP) were recorded using non-invasive technique (tailed cuff method) over period of 24 h (acute study) and 6 week (subacute study) of daily gavage. The kidney histopathology was evaluated at the end of subacute study using hematoxylin and eosin (H&E) stain. AESP at 1750 mg/kg significantly reduced SBP in the acute study (p<0.001). Similarly, MESP at 2000 mg/kg significantly reduced SBP (p<0.001). For subacute study, both AESP and MESP (at 1750 mg/kg and 2000 mg/kg, respectively) significantly reduced SBP started at week 2 (p<0.001) and continue up until week 6 of intervention (p<0.00l). In histopathology assessment, the kidney of MESP-treated SHR showed a well-preserved glomerulus and well capsulated Bowman’s capsule. In contrast, AESP did not showed the similar improvements. These results showed that despite both extracts had similar profile on blood pressure reduction, only MESP improved the histopathology of the kidney and to be potential antihypertensive agents.